Molecular characterization of SAT 2 foot-and-mouth disease virus from post-outbreak slaughtered animals: implications for disease control in Uganda - Balinda, Sabenzia N.; Belsham, Graham J.; Masembe, Charles; Sangula, Abraham K.; Siegismund, Hans R.; Muwanika, Vincent B. (Epidemiology & Infection, 2010)
In Uganda, limiting the extent of foot-and-mouth disease (FMD) spread during outbreaks involves short-term measures such as ring vaccination and restrictions of the movement of livestock and their products to and from the affected areas. In this study, the presence of FMD virus RNA was investigated in cattle samples 3 months after FMD quarantine measures had been lifted following an outbreak in 2004. Oropharyngeal tissue samples were obtained from 12 cattle slaughtered in a small town abattoir in Kiboga. FMD virus RNA was detected by diagnostic RT–PCR in nine of the 12 tissue samples. Part of the coding region for the capsid protein VP1 was amplified and sequenced. All samples were identified as belonging to the SAT 2 serotype. The implications for FMD control of both virus introduction into Uganda and the presence of carrier animals following outbreaks are discussed.
Keywords: FMD control; SAT 2; sequence divergence